Landasan Pembentukan Karakter dalam Kitab Ayyuha Al-Walad dan Relevansinya dengan Pendidikan Karakter Anak - Karlina, Reni; Wahyudi, Hakmi; Rambe, Pangadilan; Hakim, Sri Wahyuni; Hidayat, Hakmi (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to explore the formation of character in Imam Al-Ghazali's Book of Ayyuha Al-Walad and its influence on the moral education of children. The emphasis on character education is intended to deter negative conduct in children by instilling moral values rooted in religious principles, law, social norms, culture, and tradition. A qualitative research approach, incorporating a literature review, was employed for this investigation, with primary focus on Imam Al-Ghazali's work "Ayyuha Al-Walad," complemented by pertinent literature from scholarly sources. The analysis of data utilized content analysis, and the outcomes were expounded upon in the findings section. The research highlights the significance of character development in Imam Al-Ghazali's book for children's moral education, centering on values grounded in diverse principles such as knowledge, courage, self-preservation, justice, and wisdom. Imam Al-Ghazali's methods of character education encompass precision, guidance, narrative, and habituation, underscoring the importance of instilling ethical and moral values from a young age, avoiding unethical conduct, seeking closeness to the divine, and continual pursuit of knowledge